Mobile phone-based messaging for tobacco cessation in low and middle-income countries: A systematic review. (February 2021) - Krishnan, Nandita; Gu, Jiayan; Abroms, Lorien C.
Highlights: mCessation interventions could be promising in LMICs but more rigorous evaluations needed to conclusively establish efficacy. Interventions need to be tested in more diverse populations, settings and with different tobacco products. Assessing relative effectiveness of intervention characteristics could optimize mCessation intervention design. Abstract: Introduction: Mobile phone-based tobacco cessation (mCessation) interventions are effective in high-income countries but their effectiveness in low and middle-income countries (LMICs) is unclear. We aimed to assess the evidence-base for mCessation interventions in LMICs by synthesizing study characteristics and to describe intervention characteristics and content. Methods: Studies were included in this review if they evaluated an intervention that targeted tobacco users, were conducted in an LMIC, measured tobacco cessation as a primary or secondary outcome, and were primarily delivered using mobile phone (text or app-based) messaging. Data were extracted on fields pertaining to study and intervention characteristics and study quality was assessed using the Effective Public Health Practice Project tool. Screening, extraction and quality assessment were conducted by two independent reviewers. Results: Of 606 unique records, 12 articles were included. The majority of studies were methodologically weak. Methodological limitations included small sample sizes, short follow-up durations and use of self-reported outcomes. Most evaluations were conducted in upper middle-income countries with urban, adult smokers intending to quit smoking. Approximately half the interventions were bidirectional (enabled two-way messaging) and fully automated. Almost all interventions were delivered via SMS. Treatment offerings of the intervention and control groups varied widely. Conclusions: More rigorous large-scale randomized controlled trials are needed to conclusively establish the efficacy of mCessation interventions in LMICs. Interventions also need to be tested across more diverse populations and settings. Future studies should test the relative effectiveness of different intervention characteristics.